Illegal Fishing sebagai Kejahatan Korporasi Suatu terobosan Hukum pidana dalam mengadili kejahatan - Moch Iqbal (Jurnal Hukum dan Peradilan, 2012)
Coverage, insight and understanding of illegal fishing are understood and adhered to in Indonesian positive law is stealing fish and have a big impact on the economy of the country. Therefore, the essence of regulation and prosecution of illegal fishing in Indonesia should be understood in the prosecution of large-scale illegal fishing, which is generally carried out by foreign fleets, foreign vessels are illegal, which has also resulted in harming the country's economy (Indonesia) trillions of dollars each year. With the model and the type of large-scale theft and harm the national economy, the handling of the regulations should be directed at / to overcome the evils of large-scale and complicated (sophisticated), which belong to the type of crime white collar crime or corporate crime. Know and understand the ins and outs as well as the existence of corporate crime, for law enforcement is a necessity in this modern era, this paper therefore focuses on two keywords (key word) illegal fishing and corporate crime. Knowing and understanding the concepts and regulations surrounding corporate crime and illegal fishing be an important contribution in the process of law enforcement. With the understanding of illegal fishing and corporate crime will be a strong foundation for any legal practitioner, especially of law enforcement in the event proceeds and determine the type and classification of appropriate criminal and law enforcement especially true for judges to dare and did not hesitate to impose sanctions on each involved in illegal fishing or corporate offenders. With a firm and clear sentences, and certainly, the law enforcement officers not only enforce the law and justice but also has saved the country's economy, by preventing potential loss of national wealth, as the implementation of the function of law as an instrument of social engineering. Keyword: Illegal Fishing, Crime Corporation, Breaktrhough of criminal Law